Inequalities in Agricultural Subsidies in European Union - Kobus, Paweł (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The paper constitutes an attempt at comparison of subsidies level in relation to utilised agricultural area, labour force and value of production throughout EU-25 member states in years 2005 – 2013. The main objective of the paper was assessment of the level of inequalities in agricultural subsidies in European Union and evaluation of their potential trends. Using FADN data aggregated at country level the Gini coefficient was calculated for mentioned dimensions of subsidies level. Additionally sigma and beta convergence analysis were carried out for subsidies and productivity levels. The general conclusion from performed analysis was that famers in EU-10N should now perceive the subsidies level throughout EU quite fair in contrast to 2005, it is especially true in case subsidies per utilised agricultural area with drop of Gini coefficient from 0.23 to 0.15, that is by 35%. On the other hand the productivity levels are converging on much slower pace than subsidies level, for both measures of productivity the beta coefficients in convergence analysis where negative but not significant at standard 5% significance level.